Analisis kesulitan pelafalan membaca permulaan peserta didik kelas I SD - Annisa Lailatul Rahmadani; Retno Winarni; Sukarno Sukarno (Didaktika Dwija Indria, 2025)
The main problem that will be explained in this research is about reading difficulties among first-grade elementary school students. This research aims to identify reading difficulties experienced by first-grade students during the reading phase. This research uses a qualitative method with a case study approach, validity testing in data collection uses triangulation techniques of methods and sources, and data analysis uses error analysis technique guidelines. In this research, data collection from sources uses interviews, observation, and document analysis. It was then found that most first-grade students still experience difficulty in reading words due to psychological, intellectual, physiological, and environmental factors.